Distributional aspects of Ireland's fiscal adjustment - Callan, Tim; Nolan, Brian (Economic & Social Studies, 1992)
Conflicting claims about the distributional impact of Ireland's fiscal adjustment have been made. This paper clarifies the different implicit standards on which these may be based, and uses the limited available data on cash incomes and public social services to analyse the effects on poverty and inequality. For the 1986-1990 period, real incomes rose for most groups, with those reliant on the lowest social welfare rates doing well but other social welfare recipients doing less well relative to other incomes. The importance of the decline in unemployment over this period is also emphasised, making the choice of base date crucial given the very substantial rise in unemployment between 1980 and 1986. Expenditure on public social services did not bear a disproportionate share of the burden of restraining expenditure, but public expenditure on health fell significantly in real terms between 1986 and 1989. Social infrastructural investment was sharply reduced, with effects which may take some time to be felt. The paper highlights the need for micro-studies on the impact of changes in service provision, and for up-todate national household survey data, to allow the distributional impact of fiscal retrenchment to be properly assessed.
Keywords: Fiscal policy; Ireland; Poverty; Inequality; Income distribution; Tax incidence